Extreme ultraviolet holography using a laser-plasma source based on xenon/helium gas puff target. (29th December 2017) - Wachulak, P.; Sarzyński, A.; Bartnik, A.; Fok, T.; Fiedorowicz, H.
Abstract: In this paper, we present the application of partially spatially coherent extreme ultraviolet (EUV) radiation from xenon plasma from a laser-plasma source, based on a double stream gas puff target, in coherent imaging. The radiation at the wavelength of 13.5 ± 0.5 nm was employed to record Gabor-type holograms. An iterative algorithm, based on a phase retrieval technique, was developed and used to remove the twin image from the reconstructed EUV image of test objects. Using partially coherent radiation from a compact, laser-plasma source based on a double stream gas puff target, which is intrinsically incoherent, a Gabor EUV holography was successfully demonstrated.